A redação do vestibular: uma análise para além do enunciado - Cervo, Anna (Universidade do Vale do Rio dos Sinos, 2013)
The reason that underlie this study is the need to think about the writing related to the university access as coming from a situation of enunciation which mobilizes a trinitarian structure (I / you / he). Thus, our purpose is to examine this specific form of enunciation in its complexity, being it a written genre, in order to understand how the candidates institute themselves as enunciators (aiming at co-constructing the world (referent) that the University suggests through the proposal of writing), as well as acting on the allocutor concerning the situation in which they are (“intenté”). Our focus is on a corpus composed of three writings that bring critic notes, written in the text itself, made by the evaluators, concerning argumentation problems; the proposal which guides this writings is also part of this study. The questions that guide our study are: 1) which developments do the enunciative scene “vestibular writing” present? 2) How do "I" and "you" are instituted in the various enunciative developments involved in this specific situation? 3) What enunciative movements does the locutor student bring to construct the referent and to promote action on the “you” reader? Our research is based on the Enunciat ion Theory of Émile Benveniste and aligned to the group of works located within what he calls the translinguístic, a sub-area devoted to text treatment, works and complex forms of discourse. We used the pioneering work of Mello (2012), which, based on Benveniste, proposes five principles for textual treatment, in an enunciative perspective, the assumption that the meaning of a text can be inferred from its sintagmatization in the global and analytical plans. We focus our analysis on the following principles: the text is a global index of subjectivity, the text creates reference and the text constitutes a mode of action of the locutor on the allocutor. This study proves that the locutor (s) dialogues with the proponent allocutor, as well as with the reader all ocutor in different ways. In thel examined writings, the aim is the figurative board,that is, an enunciative return related to a demand is built into an intersubjective relationship with the “you”- institutional, as well as in all the writings a place is assigned to the reader in order to co-construct the meaning. It is in this space of in tersubjective that the candidate evidences his/her positions about the vestibular ́stopic, aiming at the reader’s attention. Taken as a product, these writings were considered weak in terms of the development of the topic and of argumentation. Under the enunciative view, all of them responded to the proposal, but in particular ways. Finally, we emphasize that, although the flow of the genre vestibular writing is restricted in society, it is a social practice and, as such, it mobilizes the language in its concrete usage.
Keywords: Quadro figurativo da enunciação; Redação de vestibular; Texto; Enunciado; Enunciação; Enunciative figurative board; Text; Utterance; Enunciation; ACCNPQ::Lingüística, Letras e Artes::Lingüística